Prevalence and Associated Factors of Anemia in Children Aged 6 to 59 Months in the Eastern Region of Burkina Faso - Ousmane Ouédraogo PhD; Ella Wendpouigoudinkondo Rakièta Compaoré PhD; Ousmane Ouédraogo PhD; Mediatrice Kiburente MSc; Mamoudou Hama Dicko PhD (SAGE Publishing, 2024)
Background. Anemia in children aged 6 to 59 months is a public health problem in Burkina Faso with a prevalence well above the 40% estimated by WHO globally for this age group. Aim. The objective of this study was to evaluate the prevalence and associated factors of anemia in children aged 6 to 59 months. Methods. This was a cross-sectional descriptive and analytical study. The rapid diagnostic test "hemocue" was used to measure the hemoglobin level in the blood of 486 children aged 6 to 59 months. The cut-off point for any anemia was a hemoglobin level of less than 11.0 g/dL. The chi-square test was used to analyze the anemia prevalence differences in different characteristic groups, and the multivariate logistic regression was used to analyze the relationship between the household and sociodemographic characteristics and anemia in children. The data was processed using the SPSS software. Results. Nine out of 10 children were anemic, with a prevalence of 90.9%. Prevalences were high in both Gnagna and Gourma, respectively 89.9% and 91.6%. The results of the bivariate analysis showed that the age of the child, the household head education level and the participation of the mother in activities to prevent malnutrition were significantly associated with anemia. In multivariate analysis, children aged 6 to 12 months were 3 times more likely to have anemia than children aged over 36 months. Those aged 13 to 36 months were twice as likely to have anemia as those aged over 36 months. Conclusion. There was a need to strengthen anemia interventions taking into account the age of children.